Rehabilitating Martius: Audience Response to the Hero of “Coriolanus” - McCarthy, Terence (Armenian Folia Anglistika, 2009)
The commonly held opinion that Coriolanus is the most rejected among the tragic heroes of Shakespeare stems from the political situation and the conflicting approaches towards the key issues of the class conflict. The negative reaction of the Protagonists also adversely affected the popularity of the work both at the theatre and among the audience. As Rossiter mentions, the reader fails to find a single reason to like Coriolanus throughout the tragedy. The article questions Rossiter’s approach arguing that it is due to the striking expression of emotionality at the end of the work that gives rise to the seeming intolerance towards the character. The idea dominating at the end of the novel is the re-evaluation of the evidently not political but universal ideas and values that are so distinctly incorporated in the character of Martius.